Pengaruh Kemanfaatan NPWP, Kualitas Pelayanan Perpajakan, Kesadaran Wajib Pajak, dan Sanksi Perpajakan terhadap Kepatuhan Wajib Pajak Orang Pribadi di KPP Pratama Ngawi - Shierly Anindhita, (Inisiatif: Jurnal Ekonomi, Akuntansi dan Manajemen, 2024)
Tax compliance refers to the situation of taxpayers exercising their tax authority and authority. This study aims to analyze whether partially and simultaneously the variables of compliance of Individual Taxpayers are influenced by the benefits of NPWP, quality of tax services, taxpayer awareness, and tax sanctions. The population of the study was 98,534 OP WP located in KPP Pratama Ngawi. The type of research is quantitative with a simple random sampling collection technique, and the number of samples applied is 120 respondents. This account analysis study uses SPSS software version 22 with logistic regression techniques. The results of this study prove that each of the benefits of NPWP and tax sanctions have a significant negative effect, while the quality of tax services and taxpayer awareness have a significant positive effect on Individual Taxpayer compliance. It is concluded that the overall results of this study indicate that the benefits of NPWP, quality of tax services, taxpayer awareness, and tax sanctions have an effect on Individual Taxpayer compliance.